Chlorfenapyr Crystal Polymorphism and Insecticidal Activity - Aronin, Reese; Brázda, Petr; Smith, Leilani N; Zhang, Carolyn Jin; Benedict, Jason B; Marr, Zoe Y; Rybtchinski, Boris; Weissman, Haim; Shtukenberg, Alexander G; Kahr, Bart (Crystal growth & design, 2024)
Four crystalline polymorphs of the proinsecticide chlorfenapyr [4-bromo-2-(4-chlorophenyl)-1-ethoxymethyl-5-trifluoromethyl-1H-pyrrole-3-carbonitrile] have been identified and characterized by polarized light optical microscopy, differential scanning calorimetry, Raman spectroscopy, X-ray diffraction, and electron diffraction. Three of the four structures were considered polytypic. Chlorfenapyr polymorphs show similar lethality against fruit flies (Drosophila melanogaster) and mosquitoes (Anopheles quadrimaculatus) with the least stable polymorph showing slightly higher lethality. Similar activities may be expected to be consistent with structural similarities. Knockdown kinetics, however, depend on an internal metabolic activating step, which further complicates polymorph-dependent bioavailability.